SUMBER DAYA MANUSIA KOPERASI JASA KEUANGAN SYARIAH (KJKS) DI KOTA PADANG: DILEMA ANTARA PENGELOLAAN DAN PEMAHAMAN KONSEP - M. Zaky Mubarak Lubis; Netta Agusti (Institut Agama Islam Negeri Bengkulu, 2019)
This study try to reveal the understanding of the human resources of Koperasi Jasa Keuangan Syariah (KJKS) on the basic principles of sharia economics. As a sharia microfinance institution, KJKS will face daily Muslim customers and operational systems that demand basic knowledge of Islamic economics. This study uses the focus group discussion (FGD) method with a sample target of 30 KJKS managers in the City of Padang. The sample was given 18 items pre-test questions related to the basics of Islamic economics with a choice of yes or no. We find that the main problem is still understanding the concept of Islamic economics, where there are still many cooperative managers who lack knowledge. Research shows that 39% of managers do not know clearly how the Islamic economy is. We then conducted an FGD by giving an understanding of the understanding of Islamic economics and sharia finance. It was seen an increase in the percentage graph of the understanding of cooperative managers, namely 86% of managers were able to understand the fundamentals of sharia economic concepts and sharia finance, while the other 14% were unable to understand right.